Implementasi Metode Talaqqi dalam Meningkatkan Kualitas Hafalan Al-Qur’an Siswa MTs Nurul Falah Panompuan Tapanuli Selatan - Nurliana Shinta Harahap; Fatahuddin Aziz Siregar; Hamdan Hasibuan (ISLAMIKA, 2023)
In learning tahfidzul Qur'an, one of the methods used is the talaqqi method. This method is carried out face to face or directly with teachers and students. So that this method is very suitable to be done in the learning process of tahfidz Al-Qur'an. In this method a student has to deal directly with the teacher, both himself and several students. When someone makes a mistake, the developer immediately fixes and corrects the mistake. memorizing the Qur'an Requires a technique and method that can facilitate these efforts in order to get satisfactory results. This study uses a qualitative approach. The research was conducted by observing the surrounding phenomena and analyzing them using scientific logic. Data analysis used is descriptive qualitative. The results of the study show that: 1) Implementation of the implementation of hifzul Qur'an at MTs Nurul Falah students using the talaqqi method, where two students take turns depositing their memorization directly to caregivers, both additional and deresan/muroja'ah, 2) Inhibiting factors and implementation of the talaqqi method in memorizing the Qur'an at the Nurul Falah Panompuan Islamic boarding school, from the inhibiting factors, namely the difficulties of the students in managing time, the students are less consistent. From the supporting factors, namely the existence of adequate facilities and infrastructure, the existence of good quality coaching in the field of recitation, fashahah and coaching on how to memorize and keep the memorization of the Al-Qur'an, trainers according to their fields, namely the Al-Qur'an, environmental conditions be calm.